Literature Review of The influence of Integrating Social Media as E-Learning Tools into Teaching and Learning the English Language - Alsheehri, Nada; Alenezi, Hayfa Ali; AlMutairi, Awatif; Almaqrn, Riam K. (Advances in Social Sciences Research Journal, 2020)
This study as a literature review aimed to explore the impact of the integration of social media (SM) tools into universities’ English language classrooms. Currently, the English language plays an essential and fundamental role in education. Therefore, it is crucial for learners to obtain a good understanding of the English language in the academic environment. Teaching students by traditional methods might not help to improve their English language skills. One technique that can be applied to improve learning skills quickly is utilising E-learning tools and SM in teaching strategies. Hence, this paper examines the influence of the integration of E-learning tools and strategies such as SM in teaching and learning English language in Saudi university classes. This new strategy has been chosen as it allows learners to access information anywhere without restrictions of time, and it can support them to obtain an in-depth understanding of English language content. Finally, this study will provide some recommendations and suggestions for future work.